Frequency of Macroprolactinemia in Hyperprolactinemic Women Presenting with Menstrual Irregularities, Galactorrhea, and/or Infertility: Etiology and Clinical Manifestations - Alfredo Leaños-Miranda; Karla Leticia Ramírez-Valenzuela; Inova Campos-Galicia; Rosario Chang-Verdugo; Lizbeth Zarela Chinolla-Arellano (International Journal of Endocrinology)
Aim. To determine the frequency of macroprolactinemia, its etiology, and the clinical manifestations in patients with hyperprolactinemia presenting with menstrual irregularities, galactorrhea, and/or infertility who were attended by the gynecology-endocrinology service. Methods. In a cross-sectional study, 326 hyperprolactinemic women were tested for serum prolactin (PRL) concentrations before and after chromatographic separation (gel filtration and affinity with protein G) and extraction of free PRL with polyethylene glycol (PEG). Results. Sera from 57 patients (17.5%) were found to have macroprolactinemia. The presence of macroprolactinemia was attributable to anti-PRL autoantibodies in 54 (94.7%) patients. The median serum PRL levels were similar in patients with or without macroprolactinemia (42.0 versus 38.1 ng/mL). In contrast, patients with macroprolactinemia had lower serum-free PRL levels (median 9.2 versus 31.7 ng/mL, ). Patients without macroprolactinemia had a higher frequency of galactorrhea and abnormal pituitary imagine findings (). Conclusions. We can conclude that macroprolactinemia should be considered as a benign variant, and it must be ruled out in women presenting with menstrual irregularities, galactorrhea, and/or infertility in order to investigate other causes different than hyperprolactinemia. Serum PRL precipitated with PEG is a convenient and simple procedure to screen for the presence of macroprolactinemia.